The role of visual evoked potentials in ophthalmological evaluation of a patient with optic nerve hypoplasia in septo-optic dysplasia - Nowak, Magdalena; Nowak, Karolina; Nieć, Maria; Pojda-Wilczek, Dorota (Klinika Oczna / Acta Ophthalmologica Polonica, 2023)
Optic nerve hypoplasia (ONH) is a congenital malformation which results in various degrees of visual impairment. Together, optic nerve hypoplasia, midline brain defects and dysfunction of the pituitary gland represent the characteristic triad of symptoms of septo-optic dysplasia (SOD). We describe a case of a severely intellectually disabled child with optic nerve hypoplasia, as one of the manifestations of septo-optic dysplasia syndrome. At 1 month of age, head ultrasound detected agenesis of the septum pellucidum and the corpus callosum. Magnetic resonance imaging also showed hypoplasia of the optic nerves. In ophthalmologic examination, high-intensity nystagmus was noted. Visual tracking was not observed. At 6 months of age, a visual evoked potentials (VEP) examination was performed. The results suggested the possibility of developing functional vision and led to the patient’s referral for visual rehabilitation. The VEP examination was repeated at 20 months and 5 years of age with the results showing progressive improvement of the function of the visual pathway. We aimed to depict related ophthalmic disorders of SOD and present the role of visual evoked potentials (VEP) as a useful tool for regular evaluation of patients with optic nerve hypoplasia, especially with accompanying severe developmental delay.